Three New Phenylpropanoids from the Roots of Piper taiwanense and Their Inhibitory Activities on Platelet Aggregation and Mycobacterium tuberculosis. Issue 5 (May 2014) - Chen, Si; Cheng, Ming‐Jen; Wu, Chin‐Chung; Peng, Chien‐Fang; Huang, Hung‐Yi; Chang, Hsun‐Shuo; Wang, Chyi‐Jia; Chen, Ih‐Sheng
Abstract Bioassay‐guided fractionation of the active AcOEt‐soluble fraction from the roots of Piper taiwanense has led to the isolation of two new phenylpropanoids, taiwanensols A and B (1 and 2, resp.), a new natural product, taiwanensol C (3), and 3‐acetoxy‐4‐hydroxy‐1‐allylbenzene (4). The compounds were obtained as two isomer mixtures (1/2 and 3/4, resp.). Their structures were elucidated by spectroscopic analyses, including 1D‐ and 2D‐NMR spectroscopy and mass spectrometry, and by the comparison of their NMR data with those of related compounds. Compounds 1–4 were evaluated for their antiplatelet and antitubercular activities. The mixtures 1/2 and 3/4 showed potent inhibitory activities against platelet aggregation induced by collagen, with IC50 values of 35.2 and 8.8 μM, respectively. In addition, 1/2 and 3/4 showed antitubercular activities against Mycobacterium tuberculosis H37Rv, with MIC values of 30.0 and 48.0 μg/ml, respectively.